Increasing Learning Motivation Grade IX Students Are the Pride of SMPN 6 Palu in Physical Education Learning Using the Teaching at The Right Level (TaRL) Approach - Akbar, Akbar; Purwanto, Didik; Anwar, Anwar (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This research originated from the problem of low learning motivation found in students in Physical Education, Sports and Health (PJOK) subjects. The low level of motivation affects the learning process, resulting in less than optimal results. This approach is believed to help adapt learning materials to the ability level of students, so as to stimulate their interest and motivation to be more active and enthusiastic in participating in lessons. Therefore, the main purpose of this study is to collect data and information related to efforts to increase students' learning motivation in PJOK subjects. This research method uses the type of classroom action research (PTK) by implementing the Teaching at the Right Level (TaRL) approach. This class action research was conducted in class IX Pride of SMP N 6 Palu with 34 students as subjects. Data collection and analysis techniques using quantitative percentages. The results of cycle I research showed that the percentage of learning motivation in PJOK subjects for the first dimension, namely 'Attention' reached 54% of students who participated in the learning. For the second dimension, namely 'Perseverance,' 57% of students showed this motivation, while for the third dimension, namely 'Involvement' as many as 34% of students were actively involved in learning PJOK. In cycle II, the first dimension of research, namely 'Attention,' reached 86% of the learners involved. In the second dimension, namely 'Perseverance,' 91% of learners showed motivation, while in the third dimension, namely 'Engagement,' 83% of learners were actively involved in learning PJOK. Compared to the data in cycle I, there was an increase in students' learning motivation in cycle II.